DAMPAK PELAKSANAAN JAMINAN KESEHATAN NASIONALTERHADAP HARGA OBAT DI RUMAH SAKIT ISLAM JAKARTA CEMPAKA PUTIH - Aisyah, Siti (SOCIAL CLINICAL PHARMACY INDONESIA JOURNAL, 2017)
The drug is one of the essential elements in the health services. Before JKN, drug costs reach 40%-50% of the operational costs of healthcare in Indonesia and continued to show an increase every year. In order to anticipate the high drug prices, the Ministry of health compiled National Formulary (Fornas) as guidelines in health care across the healthcare facilities in cooperation with the BPJS. The drug procurement is done through e-Catalogue system in order to ensure the availability and affordability of drugs. The e-Catalogue system has existed in Indonesia since the year 2013, but a thorough implementation in line with the implementation of national health coverage. This research aims to know the impact of the implementation of the e-Catalogue against drug prices in Islamic Hospital Jakarta Cempaka Putih. This study uses longitudinal time series methods, data collection is done in retrospective period in 2011 – 2015. The results showed a decrease in the price of the medicine reaches 90% after the implementation of the e-Catalogue program at the hospital. It can be concluded that the implementation of the program of the e-Catalogue could change drug price trends into descending.